(untitled) (Research, Society and Development, 2021)
The scientific applications related to Genetics are increasingly present in the daily lives of humanity, and from this, the teaching of genetics in schools becomes indispensable. This teaching helps to expand the knowledge of students, enabling and arousing interest in the quest to clarify their doubts and curiosities through questions and raising hypotheses, showing a creative behavior and seeking more and more information in the scientific field. Therefore, we propose the elaboration of the didactic resource “DNAaQUAFISH” for the teaching of genetics to be applied in schools, but specifically on the scientific method called environmental DNA (eDNA). This resource consists of a didactic and interactive game in which the simulation of water sample collection takes place, in a given aquatic environment, and the detection and identification of fish species using the eDNA methodology. high school and undergraduate life sciences and related fields learn about the application, importance and other issues related to eDNA and conservation genetics.